2000
DOI: 10.1046/j.1439-0531.2000.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Defence Mechanisms in Bovine Placenta and their Importance for Placental Release

Abstract: Contents Reactive oxygen species, although unavoidable intermediates, may have positive and negative effects on tissue and cells. There is some evidence that imbalance between production and neutralization of reactive oxygen species may lead to peroxidative changes of cells, disturbances of the metabolism and in consequence disorders such as, among others, the retention of fetal membranes, udder oedema and mastitis in cows. Defence mechanisms against reactive oxygen species consist of enzymatic and nonenzymati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The remaining cows that have not shed the afterbirth by 24 h, will be unable to shed until its cotyledon attachments have putrefied. There is growing evidence that overproduction of reactive oxygen species may contribute to a number of disturbances of the metabolism, resulting in the appearance of disorders such as RFM (Kankofer, 2000). Thus, it was reasonable to investigate whether vitamin E supplementation is related to a reduction of the risk for RFM.…”
Section: Mastitis -The Indirect Evidence (Immunity Studies)mentioning
confidence: 99%
“…The remaining cows that have not shed the afterbirth by 24 h, will be unable to shed until its cotyledon attachments have putrefied. There is growing evidence that overproduction of reactive oxygen species may contribute to a number of disturbances of the metabolism, resulting in the appearance of disorders such as RFM (Kankofer, 2000). Thus, it was reasonable to investigate whether vitamin E supplementation is related to a reduction of the risk for RFM.…”
Section: Mastitis -The Indirect Evidence (Immunity Studies)mentioning
confidence: 99%
“…Post‐partum uterine diseases, such as retained foetal membranes (RFM), endometritis or metritis have a major impact on dairy farms economy (Laven and Peters, ), as they are associated with poor fertility and decreased milk production, on top of the treatment costs. The aetiology of these diseases is not fully understood, but as retained placentas showed impaired antioxidant activity (Kankofer, ) and increased oxidative damage (Kankofer, ); it has been hypothesized that OS plays a key role in the improper release of the afterbirth. However, the effectiveness of vitamin E supplementation in reducing RFM incidence is controversial, with half of the studies demonstrated positive effects of vitamin E, whereas the other half showed no benefit (Politis, ).…”
Section: Benefits Of Antioxidant Supplementationmentioning
confidence: 99%
“…Cu-Zn-SOD, the main antioxidative enzyme, catalyzes the dismutation of superoxide, which is constantly formed during aerobic metabolism (Klotz et al 2003). Cu is also necessary for enzymatic action of ceruloplasmin, which has an antioxidant effect (Kankofer 2000). Cu and Zn may stimulate the synthesis of the metalothioneins -proteins having antioxidant properties (Klotz et al 2003).…”
Section: Introductionmentioning
confidence: 99%